Frequency of Thyroid Dysfunction in Diabetic Patients: Thyroid Dysfunction in Diabetic Patients - Hussain Awan, Malik Fayyaz; Affan Ali, Syed; Nadeem Qureshi, Muhammad; Hussain Shah, Masroor; Ali, Rashid; Malik, Sarwar; Ali, Qaisar (Pakistan Journal of Health Sciences, 2023)
Thyroid hormones are involved in the control of insulin secretion, beta-cell function/multiplication, liver glucose synthesis, output and peripheral utilization. Thyroid dysfunction identification and correction help in glycemic control. Objective: To know the frequency of thyroid dysfunction in diabetic patients. Methods: This descriptive cross-sectional study was done in the Medical-C Department, Ayub Teaching Hospital Abbottabad from July 2018 to August 2019. Total 150 diabetic patients were enrolled by using non-probability consective sampling. Patients were labelled as diabetics on the basis of diabetes history, anti-diabetic medications use, high blood glucose (>200mg/dl) on presentation or on previous high blood sugar reading or a high HbA1c value. Fresh venous blood sample was sent for thyroid function tests (T3, T4 and TSH). Thyroid dysfunction in our study was defined as patient having Thyroid Stimulating Hormone (TSH) value above or below the normal range. Data of patients were collected on study pro forma and was analyzed using statistical program SPSS version-20.0 Results: There were 67 (44.66%) male and 83 (55.33%) female patients. The mean age was 51.83 ± 14.52 years. Thyroid dysfunction was detected in 37 (24.66%) study participants. Out of 67 male patients, 11 (16.41%) had thyroid dysfunction and out of 83 female patients, 26 (31.32%) had thyroid dysfunction. Subclinical hypothyroidism was present in 4 (2.7%), 5 (3.3%) had hypothyroidism, 20 (13.3%) had subclinical hyperthyroidism and 8 (5.3%) had hyperthyroidism. Conclusion: This study suggests that a significant portion of diabetic patients suffer from thyroid dysfunction.